Analysis System and Procedure Deletion Goods Owned by State Center for The Development of Quality Assurance of Vocational Education in Building and Electricity Sector - Waizul Qarni; Doly Anwar Nasution; Riinawati Riinawati (LAFADZ JAYA Publisher, 2022)
State -owned commodities are all goods purchased or obtained on the weight of the state budget or obtained from other legal acquisitions. The elimination of state -owned relics is the last activity to carry out the management of state -owned relics, not a simple action from the governing board. The purpose of this research is to identify whether the system and method of removal of state -owned property is in line with the Regulation of the Minister of Finance. 83 or pmk. 06 or 2016 Regarding the rules of the method of destruction and destruction of property belonging to the state is assessed from whether the elements of the system of internal regulation of the ruler has been in accordance with the regulation of the system of internal regulation of the ruler in 2008. The research procedure used in this research is a qualitative descriptive procedure where each information is combined, analyzed and then concluded that the type of research used is qualitative descriptive. The results of this research conclude that the system and rules of the method of removal of state -owned property are in accordance with Regulation of the Minister of Finance No. 83. or PMK. 06 Deed of 2016 on the rules of the method of destruction and destruction of state property as well as the release of elements of the internal regulation system of the ruler in accordance with the Regulation of the Internal Regulation System of the ruler No. 60 of 2008.